The Association between Obstructive Sleep Apnea and Glycated Haemoglobin A1c (Hba1c) Level in Diabetes Mellitus Type II Patient - Dewi, Anna Mailasari Kusuma; Handayani, Peny; Rachma, Devi Elvina; Limijadi, Edward Kurnia Setiawan (Diponegoro International Medical Journal, 2022)
Abstract Background: Obstructive sleep apnea (OSA) is a chronic condition characterized by repetitive episodes of upper airway collapse, apnea, and arousal during sleep. OSA and type 2 diabetes mellitus (T2DM) are common comorbid conditions. Haemoglobin A1c (HbA1c) is an approximation of an individual’s average blood glucose level for the prior two to three months, and therefore is considered to be a major index for monitoring glycaemic control in diabetic patientsObjective: This study aimed to examine the association between OSA and HbA1c levels in T2DM patients.Methods: This was a cross-sectional study. The study assesses the association between OSA and HbA1c levels in 75 T2DM patients. OSA in the patient was asses with Epworth Sleepiness Scale (ESS) questionnaire. HbA1c values were obtained from the patient’s records. Data presented in mean ± SD, max, and min. Correlations analyses using Pearson correlation coefficient with p < 0.05 were considered statistically significant.Results: A total of 75 T2DM has a mean BMI were 25.26 ± 48.31 kg/m2 with mean HbA1c levels of about 7.1 ± 0.19%. The mean ESS score was 5 ± 0.429. The very weak correlation between OSA and BMI was statistically significant, r = 0.213; p = 0.047. Meanwhile, a very weak correlation between OSA and HbA1c levels was not statistically significant, r = 0.137; p = 0.242Conclusion: Among adults with T2DM, the correlation between OSA with HbA1c was not statistically significant